Motives of Cooperation and Mutual Cooperation: A Perception of the Community of Kertosari Indah Housing, Kertosari Village, Babadan District, Ponorogo Regency. - Ghaitsa Hanim Diani; I Dewa Putu Eskasasnanda (Indonesian Journal of Social Science Education (IJSSE), 2025)
This article aims to describe the forms, actors, and motivations in the implementation of mutual cooperation in the Kertosari Indah Housing environment. This article uses a qualitative approach with descriptive methods. The results show that there are two forms of mutual cooperation that develop in the community, namely routine and incidental mutual cooperation. Mutual cooperation routine includes environmental cleaning activities, morning exercises, Friday Blessings, environmental security, and donations in monthly arisan. Meanwhile, incidental mutual cooperation arises in response to urgent situations such as calamities, deaths, and celebrations. These mutual cooperation activities are inseparable from the role of community leaders such as the heads of RW, RT, and Ta'mir Mosque, as well as the active participation of resident mothers. The main motivation for residents to participate in mutual cooperation is the perceived social benefits, such as an increased sense of togetherness, friendship, and solidarity. Despite facing challenges in terms of community participation, the mobilizers continue to build engagement through personal approaches and digital communication. Mutual cooperation in Kertosari Indah Housing has proven to strengthen social relations without causing primordialism, because it is based on the collective spirit of protecting the common environment.